The Limits Of Power In Constitutional Law - نحيلي, سعيد; مخلوف, حسام (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The power is correlated to the life cycle of every political group, since the membership in any community involves subordination to its authority, i.e. to the power that define a framework for all members of society for their behavior and activities, this framework serves planned social objectives; thus Individuals respect this framework in order to maintain the social association and to prevent it from dissociation and dissolution. The current trend in constitutional jurisprudence is to restrict the power of polity and put suitable limits of it to ensure no arbitrariness from its side, and to prevent it from infringement and prejudice to the rights and freedom of individuals. The concept of sovereignty as it was described by traditional jurisprudence does not mean that power has no limits, since the release of sovereignty is relative. . Thus, the power of polity is restricted by the Goal of its existence, which is to protect the natural rights and freedom of individuals. Polity non-interference in these rights and freedom is not enough, as there should be a positive commitment from the polity to protect such rights and freedom within the limits that permitted to all to practicing it.